Kepemimpinan Pendidikan Islam dalam Perspektif Gender - Seviarica, Hilda Putri; Hikmah, Maulida Nurul; Fauzi, Robi; Hakim, Rizal Lukman (Lembaga Yasin AlSys, 2022)
This study aims to analyze the leadership of Islamic education in a gender perspective. This type of research is a literature study that is used to discuss Islamic education leadership in a gender perspective. Data collection techniques use documentation techniques by collecting data through documents, data sources that are inanimate, such as notes, letters, and photos. The results of the study indicate that the leadership of Islamic education in a gender perspective is essentially not looking at gender differences, what is needed as a leader is not to look at gender but from ability. Women and men both have their own specialties or characteristics, but basically they (men and women) are the same, so that all men's rights are also entitled to women's rights. Being a leader is not important to think about men or women, especially in Islamic religious rules there is also no prohibition against a female leader.